(untitled) (Bangladesh Journal of Medical Science, 2014)
Introduction: Lipid abnormalities are seen to be linked lack of physical activity, obesity, metabolic syndrome and diabetes mellitus. Postmenopausal women experience the changes of body composition by increasing the visceral fat. The study was aimed to explore relationship between anthropometric indices and lipid level in postmenopausal Javanese women. Methods: This cross sectional study included 34 healthy postmenopausal Javanese women, age range between 46-59 years, from Dusun Trukan, Karanggede dan Marangan Prambanan subdistrict, Sleman district. Anthropometric measurements were carried following standard procedure. Appropriate statistical tools were used to analyze data using SPSS Version 17. A p value <0.05 was taken as level of significance. Results: Abdominal circumference showed significant positive association with LDL level (r=0.289, p=0.049) but not with triglyceride, HDL level and total cholesterol level. BMI also showed significant positive association with LDL level (r=0.336, p=0.026) but not with other variables. Conclusion: The data concluded that abdominal circumference and BMI are positively association with LDL cholesterol but not with other components of the lipid profile in Javanese postmenopausal women. Further studies, however, needed to warranted to understand the causal relationship involving large number of subjects multiple centres. DOI: http://dx.doi.org/10.3329/bjms.v13i2.18293 Bangladesh Journal of Medical Science Vol.13(2) 2014 p.124-127